UPAYA QATAR DALAM MENINGKATKAN KETAHANAN PANGAN PASCA BLOKADE TAHUN 2017 - Isnawati, Elia (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
Qatar is a rich-developed country but low in food sources. It is nearly impossible to do agricultural or farming activities as Qatar located in arid and water-stress area. Local food production contributes for about 10% to the domestic food needs, therefore, Qatar heavily dependent on food imports for almost 90%. This situation leads Qatar’s food supply relying to the stability of the region and global market price. When the four Arab countries decided to impose embargo in June 5th 2017, the imports to Qatar were stopped. Qatar was forced to find food scources from other countries. This research aims to analyze how Qatar undertake to improving it’s food security as the blockade occur. This research shows Qatar’s ability to improve its food security mainly constructed by the implementation of integrated food security policy and partnership of each actor in government. Qatar managed to make policies that able achieve four aspects of food security: availability, access, utilization, and stability. Keywords: Qatar, Food Security, Blockade, Food Policy, GCC